Professional Development of Secondary School Leadership: Experiences and Expectations - nasreen, abida; Naz, Anjum; Hussain, Tariq (Journal of Peace, Development and Communication, 2021)
This study is an attempt to explore the formal and informal professional training experiences of principals. The study also explored the barriers faced by them in the pursuit of professional development programs/training. This qualitative research study was based on interpretive paradigm. The data was collected through in-depth interviews. A thematic analysis approach was used to analyze data. The results revealed that the principals come across many negative and positive situations every day. Some of them were never given the opportunity for professional training. Others stated some professional and personal problems which generally create hurdles in the pursuit of professional development programs. They also emphasize the importance of teamwork. It was suggested that here should be a conduct of separate administrative trainings specifically designed for school principals/ heads and trainers/ resource persons should be highly qualified in the field of educational administration.